Precarity and ageing : understanding insecurity and risk in later life - Grenier, Amanda; Phillipson, Chris; Settersten, Richard A., Jr., 1964- (Ageing in a global context., 2020)
What risks and insecurities do older people face in a time of both increased longevity and widening inequality? This edited collection develops an exciting new approach to understanding the changing cultural, economic and social circumstances facing different groups of older people. Exploring a range of topics, the chapters provide a critical review of the concept of precarity, highlighting the experiences of ageing that occur within the context of societal changes tied to declining social protection. Drawing together insights from leading voices across a range of disciplines, the book underscores the pressing need to address inequality across the life course and into later life.--